CYP2E1 and Oxidative Liver Injury by Alcohol - Lu, Yongke (2007)
Ethanol-induced oxidative stress appears to play a major role in mechanisms by which ethanol causes liver injury. Many pathways have been suggested to contribute to the ability of ethanol to induce a state of oxidative stress. One central pathway appears to be the induction of cytochrome P450 2E1 (CYP2E1) by ethanol. CYP2E1 metabolizes and activates many toxicological substrates, including ethanol, to more reactive, toxic products. Levels of CYP2E1 are elevated under a variety of physiological and pathophysiological conditions, and after acute and chronic alcohol treatment. CYP2E1 is also an effective generator of reactive oxygen species such as the superoxide anion radical and hydrogen peroxide, and in the presence of iron catalysts, produces powerful oxidants such as the hydroxyl radical. This Review Article summarizes some of the biochemical and toxicological properties of CYP2E1, and briefly describes the use of cell lines developed to constitutively express CYP2E1 in assessing the actions of CYP2E1. Possible therapeutic implications for treatment of alcoholic liver injury by inhibition of CYP2E1 or CYP2E1-dependent oxidative stress will be discussed, followed by some future directions which may help to understand the actions of CYP2E1 and its role in alcoholic liver injury.